Study of the rate limiting steps and degradation of a GDC impregnated La0.6Sr0.4Co0.8Fe0.2O3-δ cathode - Ascolani Yael, Julian Esteban (2017)
In this work, a Solid Oxide Fuel Cell (SOFC) cathode surface modification by nanoparticle impregnation was carried out. La0.6Sr0.4Co0.8Fe0.2O3-δ (LSCF) ceramic cathodes impregnated with Ce0.8Gd0.2O3-δ (GDC) nanoparticles were characterized with scanning (SEM) and transmission (TEM) electron microscopy. The electrochemical response as a function of temperature, oxygen partial pressure (pO2) (10-4 < pO2< 1 atm) and time was evaluated by electrochemical impedance spectroscopy (EIS). We obtained reproducible and homogeneous impregnations, which reduce the total cathode's polarization resistance more than 20% in the temperature range between 400°C and 800°C and during 500 h at 700°C. The impregnated cathode was found to be electrochemically limited by the same processes as the nonimpregnated cathode, namely gas diffusion, ion bulk diffusion and dissociative adsorption. The impregnation produced a reduction of more than 20% of the oxygen surface resistance; such difference remained stable through 500h of continuous operation at 700°C.